Astrophysics - Tabanli, Mustafa (New Jersey : Everest Production, 2008)
Explores astrophysics, the branch of astronomy that deals with the physics of the universe, including the physical properties of celestial objects, as well as their interactions and behavior.
Executive producer, Nasuhi Yurt.
Host : MaryLynn Schiavi.
Keywords: Astrophysics; Physics; Astronomy